Continuous flow synthesis of arylhydrazines via nickel/photoredox coupling of tert-butyl carbazate with aryl halides. Issue 93 (5th November 2020) - Mata, Alejandro; Tran, Duc N.; Weigl, Ulrich; Williams, Jason D.; Kappe, C. Oliver
Abstract : We present the first nickel/photoredox coupling of (hetero)aryl halides with hydrazine derivatives, allowing access to valuable arylhydrazine intermediates in flow. Abstract : Nickel/photoredox catalyzed C–N couplings of hydrazine-derived nucleophiles provide a powerful alternative to Pd-catalyzed methods. This continuous-flow photochemical protocol, optimized using design of experiments, achieves these couplings in short residence times, with high selectivity. A range of (hetero)aryl bromides and chlorides are compatible and understanding of process stability/reactor fouling has been discerned.